Nghiên cứu ảnh hưởng của phụ gia chống bức xạ tử ngoại đến tính chất cơ học và khả năng chậm lão hóa của vật liệu polyme compozit trên cơ sở dầu lanh epoxy hóa - Diệu, Trần Vĩnh; Tuấn, Phạm Anh; Phúc, Bạch Trọng (Vietnam Journal of Chemistry, 2015)
The photon energy in solar radiation is the most damaging excitator of the outdoor environment in polymer composite (PC) materials which include epoxidized linseed oil polymer. In this study, the effect of ultraviolet (UV) radiation on the change of PC material surface appearance and the reduction in mechanical properties was investigated. In addition, in order to diminish the effect of UV radiation on to polymer matrix, in this study anti-UV addtives was introduced. In which, UV-absorber methanone, 2-hydroxy-4-(octyloxy)-phenyl  (MHOP) and hindered amine light stabilizers (HALS) bis (1-octyloxy-2,2,6-tetramethyl-4-piperidyl) sebacate (BOTPS) was used. The results showed that in the presence of  2.0 %wt. MHOP and 3.0 %wt. BOTPS can be  restricted the degree of PC materials  surface change and reduction of the composite’s mechanical properties.